Hair androgen concentrations and depressive disorders in adolescents from the general population. (September 2021) - Kische, H.; Voss, C.; Haring, R.; Ollmann, T.M.; Pieper, L.; Kirschbaum, C.; Beesdo-Baum, K.
Abstract : Background: Although the link between androgens and depression is well established in adults, the effect of cofactors on this association are less clearly understood in youth. Methods: Epidemiological cohort study of adolescents in Dresden, Germany. Analyses comprised data of 985 individuals assessed at baseline (512 individuals at follow-up). We investigated sex-specific multivariable regression models for cross-sectional/longitudinal associations of hair testosterone, dehydroepiandrosterone (DHEA), and their cortisol ratios with major depressive disorder (MDD) and dimensional depression scores (PROMIS). Results: Cross-sectional analyses yielded inverse associations of testosterone and DHEA with MDD (b: 0.96, 95%CI: 0.91-0.99, p<0.05) and of ratio cortisol/DHEA with PROMIS in males (b: -0.01, 95%CI: -0.02-(-0.004)), p<0.01) in males but not in females. Conclusions: The present observational cohort study showed no consistent association of hair androgen concentrations with depressive disorders. However, findings provide some support for the association between androgens and depression in males. Longitudinal research designs are needed to understand the interplay between androgens, depression, and developmental factors in youth.